Serial burn - Eason, Lynette (Eason, Lynette. Lake City heroes., 2025)
"Ever since Fire Marshal Jesslyn McCormick lost her family in a fire, she's been looking: for the arsonist, for a reason, for relief from the guilt of surviving. In a twisty tale of revenge, forgiveness, and justice, Jesslyn and FBI Special Agent Nathan Carlisle team up to find the answers--if they can keep her alive long enough to ask the questions"--